A generalization of WUU rings - Danchev, P. V. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We define the class of UNI rings and present the results of their comprehensive investigations in connection with cleanrings, namely, our main result describes commutative UNI clean rings up to an isomorphism. This new concept is acommon generalization of the so-called UU rings examined by Danchev – Lam in (Publ. Math. Debrecen, 2016) and ofthe so-called WUU rings studied by the author in (Tsukuba J. Math., 2016).